2013
DOI: 10.1364/boe.4.001390
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization-dependent changes in EGFP fluorescence lifetime measured by time-resolved flow cytometry

Abstract: Intracellular protein transport and localization to subcellular regions are processes necessary for normal protein function. Fluorescent proteins can be fused to proteins of interest to track movement and determine localization within a cell. Currently, fluorescence microscopy combined with image processing is most often used to study protein movement and subcellular localization. In this contribution we evaluate a high-throughput time-resolved flow cytometry approach to correlate intracellular localization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 49 publications
(57 reference statements)
2
31
0
Order By: Relevance
“…3.1–3.3 ns)293435. Alternatively, when the fluorescent protein expressing E. coli were engulfed by RAW264.7 cells, and trapped in the membrane-like vacuoles where a decrease of pH is known to occur, the fluorescence lifetime shifted by 1 ns.…”
Section: Discussionmentioning
confidence: 99%
“…3.1–3.3 ns)293435. Alternatively, when the fluorescent protein expressing E. coli were engulfed by RAW264.7 cells, and trapped in the membrane-like vacuoles where a decrease of pH is known to occur, the fluorescence lifetime shifted by 1 ns.…”
Section: Discussionmentioning
confidence: 99%
“…Reports that the average GFP fluorescence lifetime of maltreated cells changes may be related to this effect too (Nakabayashi et al, 2008a). Moreover, using flow cytometry and the GFP fluorescence lifetime as the cytometric parameter, it has been shown that the GFP fluorescence lifetime can be correlated to changes in the subcellular localization of GFP-LC3 fusion protein to the autophagosome during autophagy (Gohar et al, 2013).…”
Section: Flim To Map the Refractive Indexmentioning
confidence: 99%
“…We and others have demonstrated different versions of time-resolved flow cytometry [3,[7][8][9][10][11][12][13][14], and the main objective for augmenting flow cytometers to detect fluorescence lifetimes is to enhance cytometric data with a quantitative parameter that is independent of the measured fluorescence intensity [11,[15][16][17]. As a parameter, fluorescence lifetime can be used to discriminate among spectrally overlapping fluorescence signals as well as to validate the fluorescence intensity changes that arise from quenched fluorophores such as during Förster resonance energy transfer (FRET) events like those arising from changes in association state of tagged cytoplasmic proteins.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of cellular applications might include use of fluorescence lifetimes to discriminate among multiple exogenous fluorophores labeled to cell surface receptors (i.e. immunofluorescence), to correlate the fluorescent protein intracellular location with fluorescence decay kinetics, to sort cells that express fluorescent proteins with high quantum yields (because QY is proportional to the fluorescence lifetime), or to detect shifts in cellular metabolism for large populations of cell using autofluorescence lifetime shifts of the bound state of NADH [15,[18][19][20][21]. These listed applications are but a few among many reasons to measure the decay kinetics of fluorescent species in order to understand intracellular biochemistry and molecular events, or to detect protein conformational changes.…”
Section: Introductionmentioning
confidence: 99%